ANALISIS KEPUASAN WAJIB PAJAK: PENDEKATAN TERHADAP PENGGUNAAN TEKNOLOGI INFORMASI DAN SELF ASSESSMENT - Kesdu, Purwito (KELOLA, 2013)
The aim of this study is to investigate the influence of using Information technology and self assessment system to tax prayersâ Satisfaction. The Hypothesis which have been formulated in this research are: there is direct and indirect influence of using Information technology and self assessment system to tax prayerâs Satisfaction. The research is a survey to tax payers in Surakarta, Data have been collected with quesionaries as 100 respondents are processed with, validity and reliability test, the regression analysis, t test, F test and test of R2 . The t test result shows that there is an influence of using Information technology and self assessment system to tax prayers Satisfaction. The F test result shows that there is an influence of using Information technology and self assessment system to tax prayers Satisfaction simultaneously. From test of R2 shows that the independent variable can explain performance about 67,6% and 32,4% explained by other variables: Keyword: using Information technology, self assessment system, tax prayers Satisfaction